2016
DOI: 10.1002/adma.201604825
|View full text |Cite
|
Sign up to set email alerts
|

Soft Microrobots Employing Nonequilibrium Actuation via Plasmonic Heating

Abstract: A soft microrobot composed of a microgel and driven by the light‐controlled nonequilibrium dynamics of volume changes is presented. The photothermal response of the microgel, containing plasmonic gold nanorods, enables fast heating/cooling dynamics. Mastering the nonequilibrium response provides control of the complex motion, which goes beyond what has been so far reported for hydrophilic microgels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
224
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 163 publications
(229 citation statements)
references
References 40 publications
3
224
0
2
Order By: Relevance
“…[11,12] This phenomenon was recently explored for soft microrobots. [13,14] For basic understanding and applications, it is important to quantify thermodynamic parameters of the temperature-induced phase transition process. It was shown that for free PNIPAm polymers in aqueous solution the phase transition temperature depends on the molecular weight and the hydrophilic or hydrophobic end functionalization.…”
Section: Doi: 101002/marc201700362mentioning
confidence: 99%
“…[11,12] This phenomenon was recently explored for soft microrobots. [13,14] For basic understanding and applications, it is important to quantify thermodynamic parameters of the temperature-induced phase transition process. It was shown that for free PNIPAm polymers in aqueous solution the phase transition temperature depends on the molecular weight and the hydrophilic or hydrophobic end functionalization.…”
Section: Doi: 101002/marc201700362mentioning
confidence: 99%
“…We demonstrate that the temperature modulation or exchanging the solvent allows for reversible shifting of plasmonic resonances in the near infrared part of the spectrum by up to 150 nm, which exceeds the spectral width of the resonance as low as 13 nm and allows its complete switching “on” and “off.” The potential capabilities for biosensing with the tethered configuration employing a hydrogel that can be post‐modified with protein ligands are assessed for the refractometric localized surface plasmon resonance biosensors, where a figure of merit as high as 29 was observed. The plasmonic architectures with on‐demand tunable optical properties also hold potential to be employed as active plasmonic substrates in other biosensor modalities taking advantage of plasmonically amplified optical spectroscopy and in miniature machines . For instance, the tunable plasmonic wavelength may find its applications in multiplexed plasmon‐enhanced fluorescence sensing or for the fine‐tuning of surface‐enhanced Raman spectroscopy enhancement for specific vibration bands.…”
Section: Resultsmentioning
confidence: 99%
“…The plasmonic architectures with on-demand tunable optical properties also hold potential to be employed as active plasmonic substrates in other biosensor modalities taking advantage of plasmonically amplified optical spectroscopy [17,46] and in miniature machines. [47] For instance, the tunable plasmonic wavelength may find its applications in multiplexed plasmonenhanced fluorescence sensing or for the fine-tuning of surface-enhanced Raman spectroscopy enhancement for specific vibration bands.…”
Section: Refractometric Sensing Measurementsmentioning
confidence: 99%
“…Just to name a few, ongoing debates are held on cononsolvency phenomena, salting‐in and salting‐out effects, stimuli‐triggered aggregation mechanisms, and on the origins of upper and lower critical solution temperature‐type (UCST‐ and LCST‐type, respectively) behavior . Further remarkable research goes into the direction of time‐programmed stimuli‐responsive self‐assembly and superfast actuation …”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Further remarkable research goes into the direction of time-programmed stimuli-responsive self-assembly 28,29 and superfast actuation. [30][31][32] Controlled polymerization techniques offer the possibility to tailor the switchable material according to the demand of its envisaged application, for example when two or more stimuli-responsive building blocks are combined in statistical or block copolymers. 33,34 For instance, UCST-b-LCST-type thermoresponsive block copolymers can show so-called schizophrenic self-assembly in water, meaning that their micellar core-shell structure can be inverted under proper conditions.…”
Section: Introductionmentioning
confidence: 99%